Fiscal Imbalance and Winnipeg: A Century of Response - Hum, Derek; Strain, Frank; Strain, Michelle (Urban History Review / Revue d'histoire urbaine, 1986)
A growing gap between municipal expenditures and municipal revenues is often characterized as fiscal imbalance or fiscal distress. It is well known that municipal governments in Canada have no constitutional standing and that their revenue sources are meagre, slow-growing and inadequate. At the same time, municipalities are obliged to provide their citizens more and more services, thereby resulting in continuous expenditure growth. This paper examines the extent of fiscal imbalance throughout the past century for the City of Winnipeg. It attempts not only to portray the reaction of a specific city to fiscal imbalance pressures, but also to relate the response to the economic orthodoxy and condition of its period.The paper begins with a description of the main hypothesis concerning the cause of urban fiscal crisis and presenting an accounting framework for examining indicators of fiscal distress. A survey of the fiscal experience of Winnipeg is then presented, from incorporation in 1874 to 1984 by dividing the century into five periods. The paper concludes that the reactions of municipal government to fiscal imbalance is conditioned just as much by the reigning economic orthodoxy of what constitutes a fiscally responsible action as it does by external factors such as revenue flows and public demand for services.